Pentingnya Meningkatkan Kebugaran Jasmani pada Anak Sekolah Dasar Melalui Olahraga dan Aktivitas Fisik - Mulyana, Agus; Salsabil, Alfi Mardiyah; Muthmainah, Annisa; Aulia, Naifa Fae; Syifa, Nazwa Al; Noviyanti, Netha Salwa; Ristianti, Risma (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to examine the importance of improving physical fitness in elementary school (SD) children through sports and physical activity. The method used is a literature study by analyzing various relevant literature. This research will explore various literature, such as books, articles, journals, research reports, and other relevant sources. Data analysis is carried out qualitatively with stages of data reduction, data presentation, and conclusion drawing. The results showed that physical fitness is very important for elementary school children to support their growth and development optimally. Regular sports and physical activity can improve the physical fitness of elementary school children, by providing a variety of physical, mental, and social benefits. The primary school curriculum in Indonesia has incorporated physical education, sports, and health subjects to increase students' physical activity. However, additional efforts are still needed to ensure students remain active outside of class hours. In conclusion, improving physical fitness in elementary school children through sports and physical activity should be a priority in basic education